Westonci.ca is the premier destination for reliable answers to your questions, provided by a community of experts. Explore thousands of questions and answers from knowledgeable experts in various fields on our Q&A platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
Certainly! Let's solve the given integral step by step.
We start by performing a partial fraction decomposition of the integrand.
### Step 1: Partial Fraction Decomposition
Given the integral:
[tex]\[ \int \frac{3x+5}{(x+1)(x-1)^2} \, dx \][/tex]
We want to decompose [tex]\(\frac{3x+5}{(x+1)(x-1)^2}\)[/tex] into simpler fractions. The appropriate form for the partial fraction decomposition is:
[tex]\[ \frac{3x+5}{(x+1)(x-1)^2} = \frac{A}{x+1} + \frac{B}{x-1} + \frac{C}{(x-1)^2} \][/tex]
### Step 2: Finding Coefficients [tex]\(A\)[/tex], [tex]\(B\)[/tex], and [tex]\(C\)[/tex]
To find the constants [tex]\(A\)[/tex], [tex]\(B\)[/tex], and [tex]\(C\)[/tex], we write:
[tex]\[ 3x + 5 = A(x-1)^2 + B(x+1) + C(x+1)(x-1) \][/tex]
Expanding and simplifying:
[tex]\[ 3x + 5 = A(x^2 - 2x + 1) + B(x + 1) + C(x^2 - 1) \][/tex]
[tex]\[ 3x + 5 = Ax^2 - 2Ax + A + Bx + B + Cx^2 - C \][/tex]
[tex]\[ 3x + 5 = (A + C)x^2 + (-2A + B)x + (A + B - C) \][/tex]
By equating coefficients of [tex]\(x^2\)[/tex], [tex]\(x\)[/tex], and the constant term, we get three equations:
1. For [tex]\(x^2\)[/tex]: [tex]\(A + C = 0\)[/tex]
2. For [tex]\(x\)[/tex]: [tex]\(-2A + B = 3\)[/tex]
3. For constants: [tex]\(A + B - C = 5\)[/tex]
From equation (1):
[tex]\[ C = -A \][/tex]
Substitute [tex]\(C = -A\)[/tex] into equations (2) and (3):
[tex]\[ -2A + B = 3 \quad \text{(2)} \][/tex]
[tex]\[ A + B - (-A) = 5 \quad \text{(3)} \][/tex]
Simplifying equation (3):
[tex]\[ A + B + A = 5 \][/tex]
[tex]\[ 2A + B = 5 \quad \text{(3)} \][/tex]
Now we have:
1. [tex]\(-2A + B = 3\)[/tex]
2. [tex]\(2A + B = 5\)[/tex]
Subtract equation (1) from equation (2):
[tex]\[ [(2A + B) - (-2A + B)] = 5 - 3 \][/tex]
[tex]\[ 4A = 2 \][/tex]
[tex]\[ A = \frac{1}{2} \][/tex]
[tex]\[ C = -A = -\frac{1}{2} \][/tex]
Now substitute [tex]\(A = \frac{1}{2}\)[/tex] into either equation to find [tex]\(B\)[/tex]:
[tex]\[ 2(\frac{1}{2}) + B = 5 \][/tex]
[tex]\[ 1 + B = 5 \][/tex]
[tex]\[ B = 4 \][/tex]
So, we have:
[tex]\[ A = \frac{1}{2}, \quad B = 4, \quad C = -\frac{1}{2} \][/tex]
Thus the partial fraction decomposition is:
[tex]\[ \frac{3x+5}{(x+1)(x-1)^2} = \frac{\frac{1}{2}}{x+1} + \frac{4}{x-1} - \frac{\frac{1}{2}}{(x-1)^2} \][/tex]
### Step 3: Integrating Each Term
Now, we integrate each term separately:
[tex]\[ \int \frac{3x+5}{(x+1)(x-1)^2} \, dx = \int \left( \frac{\frac{1}{2}}{x+1} + \frac{4}{x-1} - \frac{\frac{1}{2}}{(x-1)^2} \right) \, dx \][/tex]
[tex]\[ = \frac{1}{2} \int \frac{1}{x+1} \, dx + 4 \int \frac{1}{x-1} \, dx - \frac{1}{2} \int \frac{1}{(x-1)^2} \, dx \][/tex]
Integrating each term:
[tex]\[ \int \frac{1}{x+1} \, dx = \ln|x+1| + C_1 \][/tex]
[tex]\[ \int \frac{1}{x-1} \, dx = \ln|x-1| + C_2 \][/tex]
[tex]\[ \int \frac{1}{(x-1)^2} \, dx = -\frac{1}{x-1} + C_3 \][/tex]
Combining these, we get:
[tex]\[ \frac{1}{2} \ln|x+1| + 4 \ln|x-1| - \frac{1}{2} \left( -\frac{1}{x-1} \right) + C \][/tex]
Simplifying this, we have:
[tex]\[ \frac{1}{2} \ln|x+1| + 4 \ln|x-1| + \frac{1}{2(x-1)} + C \][/tex]
Using logarithm properties, we can combine the logarithms:
[tex]\[ \boxed{-\frac{1}{2} \ln|x-1| + \frac{1}{2} \ln|x+1| - \frac{4}{x-1} + C} \][/tex]
This is the final answer:
[tex]\[ \boxed{-\frac{1}{2} \ln|x-1| + \frac{1}{2} \ln|x+1| - \frac{4}{x-1} + C} \][/tex]
We start by performing a partial fraction decomposition of the integrand.
### Step 1: Partial Fraction Decomposition
Given the integral:
[tex]\[ \int \frac{3x+5}{(x+1)(x-1)^2} \, dx \][/tex]
We want to decompose [tex]\(\frac{3x+5}{(x+1)(x-1)^2}\)[/tex] into simpler fractions. The appropriate form for the partial fraction decomposition is:
[tex]\[ \frac{3x+5}{(x+1)(x-1)^2} = \frac{A}{x+1} + \frac{B}{x-1} + \frac{C}{(x-1)^2} \][/tex]
### Step 2: Finding Coefficients [tex]\(A\)[/tex], [tex]\(B\)[/tex], and [tex]\(C\)[/tex]
To find the constants [tex]\(A\)[/tex], [tex]\(B\)[/tex], and [tex]\(C\)[/tex], we write:
[tex]\[ 3x + 5 = A(x-1)^2 + B(x+1) + C(x+1)(x-1) \][/tex]
Expanding and simplifying:
[tex]\[ 3x + 5 = A(x^2 - 2x + 1) + B(x + 1) + C(x^2 - 1) \][/tex]
[tex]\[ 3x + 5 = Ax^2 - 2Ax + A + Bx + B + Cx^2 - C \][/tex]
[tex]\[ 3x + 5 = (A + C)x^2 + (-2A + B)x + (A + B - C) \][/tex]
By equating coefficients of [tex]\(x^2\)[/tex], [tex]\(x\)[/tex], and the constant term, we get three equations:
1. For [tex]\(x^2\)[/tex]: [tex]\(A + C = 0\)[/tex]
2. For [tex]\(x\)[/tex]: [tex]\(-2A + B = 3\)[/tex]
3. For constants: [tex]\(A + B - C = 5\)[/tex]
From equation (1):
[tex]\[ C = -A \][/tex]
Substitute [tex]\(C = -A\)[/tex] into equations (2) and (3):
[tex]\[ -2A + B = 3 \quad \text{(2)} \][/tex]
[tex]\[ A + B - (-A) = 5 \quad \text{(3)} \][/tex]
Simplifying equation (3):
[tex]\[ A + B + A = 5 \][/tex]
[tex]\[ 2A + B = 5 \quad \text{(3)} \][/tex]
Now we have:
1. [tex]\(-2A + B = 3\)[/tex]
2. [tex]\(2A + B = 5\)[/tex]
Subtract equation (1) from equation (2):
[tex]\[ [(2A + B) - (-2A + B)] = 5 - 3 \][/tex]
[tex]\[ 4A = 2 \][/tex]
[tex]\[ A = \frac{1}{2} \][/tex]
[tex]\[ C = -A = -\frac{1}{2} \][/tex]
Now substitute [tex]\(A = \frac{1}{2}\)[/tex] into either equation to find [tex]\(B\)[/tex]:
[tex]\[ 2(\frac{1}{2}) + B = 5 \][/tex]
[tex]\[ 1 + B = 5 \][/tex]
[tex]\[ B = 4 \][/tex]
So, we have:
[tex]\[ A = \frac{1}{2}, \quad B = 4, \quad C = -\frac{1}{2} \][/tex]
Thus the partial fraction decomposition is:
[tex]\[ \frac{3x+5}{(x+1)(x-1)^2} = \frac{\frac{1}{2}}{x+1} + \frac{4}{x-1} - \frac{\frac{1}{2}}{(x-1)^2} \][/tex]
### Step 3: Integrating Each Term
Now, we integrate each term separately:
[tex]\[ \int \frac{3x+5}{(x+1)(x-1)^2} \, dx = \int \left( \frac{\frac{1}{2}}{x+1} + \frac{4}{x-1} - \frac{\frac{1}{2}}{(x-1)^2} \right) \, dx \][/tex]
[tex]\[ = \frac{1}{2} \int \frac{1}{x+1} \, dx + 4 \int \frac{1}{x-1} \, dx - \frac{1}{2} \int \frac{1}{(x-1)^2} \, dx \][/tex]
Integrating each term:
[tex]\[ \int \frac{1}{x+1} \, dx = \ln|x+1| + C_1 \][/tex]
[tex]\[ \int \frac{1}{x-1} \, dx = \ln|x-1| + C_2 \][/tex]
[tex]\[ \int \frac{1}{(x-1)^2} \, dx = -\frac{1}{x-1} + C_3 \][/tex]
Combining these, we get:
[tex]\[ \frac{1}{2} \ln|x+1| + 4 \ln|x-1| - \frac{1}{2} \left( -\frac{1}{x-1} \right) + C \][/tex]
Simplifying this, we have:
[tex]\[ \frac{1}{2} \ln|x+1| + 4 \ln|x-1| + \frac{1}{2(x-1)} + C \][/tex]
Using logarithm properties, we can combine the logarithms:
[tex]\[ \boxed{-\frac{1}{2} \ln|x-1| + \frac{1}{2} \ln|x+1| - \frac{4}{x-1} + C} \][/tex]
This is the final answer:
[tex]\[ \boxed{-\frac{1}{2} \ln|x-1| + \frac{1}{2} \ln|x+1| - \frac{4}{x-1} + C} \][/tex]
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.